Bauran Pemasaran Dalam Pembentukan Keunggulan Bersaing Pada Usaha Mikro Kuliner - Khairul Zaman; Mashadi Mashadi; Gen Gen Gendalasari (Program Vokasi dan LPPM IBI Kesatuan, 2023)
The study aims to determine how the application of the Marketing Mix on Pecel Lele Konco Dewe forms its Competitive Advantages. This study was made to determine and analyze what marketing strategy is suitable for Pecel Lele Konco Dewe. The research method used in the form of SWOT analysis and descriptive analysis method using qualitative approach. Desciptive analysis is an analysis that is not in the form of numbers, but in the form of a series of information obtained and then dug deeper than the research result obtained. Therefore, as a writer, i must know the cirumstances, situations, and conditions that exist in Pecel Lele Konco Dewe and what internal and external factors affect the marketing strategy of Pecel Lele Konco Dewe. The data collection technique carried out by the author is to conduct interviews and direct observations on the owner of Pecel Lele Konco Dewe. In addition, to support the validity of this research, additional supporting data from reference books and the other sources related to this research are needed. The data obtained from the result of data collection and observation are then analyzed using SWOT analysis to find out what indicators are the strengths, weaknesses, opportunities, and threats of the marketing strategy carried out by Pecel Lele Konco Dewe. Through the result of the analysis shown by the Cartesian diagram, Pecel Lele Konco Dewe’s positions is in quadrant I, which is to support an aggressive strategy with the implementation of a growth oriented strategy. The position in this quadrant is a very profitable position of Pecel Lele Konco Dewe where Pecel Lele Konco Dewe has the strength so that it can take advantage of the opportunies that exist as well possible. Keyword: Marketing Mix, Competitive Advantages, and SWOT Analysis